Karakteristik Campuran Beraspal jenis (Asphalt Concrete Binder Coarse) AC/BC Menggunakan Pasir Alam Kampar Dengan Pengujian Marshall Berdasarkan Spesifikasi Bina Marga 2010 - Armi, Rizki Sahfutra; Sentosa, Leo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
One of producing areas of natural sand in Riau province is natural sand from Kampar River, when compared with the existence of stone ash, natural sand is easier to obtained and more economical because it does not have to go through crushing process by stone crusher. In accordance with Specifications of Bina Marga 2010, the use of natural sand for the asphalt concrete mixture (AC) should not exceed 15% of total weight of mixture aggregate. Thus it is important to know the efficiency of using natural sand on the asphalt concrete mixture (AC) to get optimum utilization. This research is to determine the optimum bitumen content (OBC) and the optimum content of natural sand (OCNS) which can be used on the asphalt concrete binder coarse mixture (AC/BC) fine gradation. The fine aggregate variations of natural sand used was 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, and 40% of the total weight of the mixture of aggregate. The additions of natural sand on the asphalt concrete binder coarse mixture (AC/BC) can decrease values of the optimum bitumen content (OBC) and density. An optimum content of natural sand (OCNS) for the asphalt concrete binder coarse mixture (AC/BC) was obtained by additional of 10% natural sand with the optimum bitumen content (OBC) of 6,45% which the value of the stability of 1.745,96 kg. If natural sand is unlimited as in the Specification of Bina Marga 2010, so possibilities on the additional of natural sand on the asphalt concrete binder coarse mixture (AC/BC) is up to 25 % .Keywords: Natural sand, Asphalt Concrete Binder Coarse (AC/BC), Spesification of Bina Marga 2010, and Marshall characteristic.